Improving Pre-Hospital Emergency Care: A Review of Interventions Led by EMS Technicians - Saif Thamer Ghazi Aljuaid; Abdulrahman Saud S Aljuaid; Mohammed Hamed Mohammed Alharbi (International Journal of Medical Toxicology and Legal Medicine, 2025)
Emergency Medical Services (EMS) technicians are pivotal in delivering life-saving interventions during the critical pre-hospital phase of patient care. As the frontline responders, their scope of practice has significantly expanded over recent years to include advanced procedures in airway management, cardiovascular support, trauma care, and community-based health services. This review aims to synthesize current literature on EMS technician-led interventions and their effectiveness in improving patient outcomes in pre-hospital settings. Through a systematic search of peer-reviewed articles published between 2015 and 2024, the study identifies key intervention domains, assesses their clinical effectiveness, and highlights innovations such as community paramedicine and pre-hospital telemedicine. The findings demonstrate that EMS technician interventions contribute to improved survival rates, reduced time to definitive care, and enhanced continuity of care. However, challenges such as training variability, scope limitations, and integration with broader healthcare systems remain. The review concludes with recommendations for standardizing EMS education, expanding community roles, and strengthening interdisciplinary coordination to optimize pre-hospital emergency care outcomes.